Analysis on the Need of Social Service of Poor Fishermen Families - Chatarina Rusmiyati; Akhmad Purnama (Jurnal Penelitian Kesejahteraan Sosial, 2016)
Indonesian inhabitants who live along seashores still depends their lives on fishery. Fishermen are like a group of poor people living in slum areas along the coast and it is difficult to acheive welfare society. The study meant to know and analyse the need of social service for poor fishermen family. The study was held in Padang Pariaman Regency, West Sumatera Province, subjects of the study were 30 poor fishermen families and field guidance official. Data were analysed through qualitative-descriptive technique. The study found that poor fishermen families condition in Padang Pariaman were low income, under regional minimum wage Rp 1.630.000,- with members of the family they have to support more than three people. The educational background was also low, primary school or its equivalent. The majority have the houses decended from their parents, some living with their parents or parents in law. House conditions some permanent and some semipermanent. The majority benefited health care to local central community health care and some to privat doctors and assistants. They ate enough, three and two times dailly. Social and guidance services they needed, sort of training and motivating to enhance knowledge, reference, and to grow sense of entrepreneurship; Monetary management elucidacion to manage families fund including saving habit, and capital assistance and guidance so that fishermen courage to put up capital to develop their business. The Ministry of social Affairs should optimize the role of social to give social guidance and service to help enhance fishermen lives quality, motivate and give skill supplement on fishermen and their families so that their welfare quality raising.